All Treatments in Tinnitus Are Experimental, Controversial, and Futuristic: A Comment on “Experimental, Controversial, and Futuristic Treatments for Chronic Tinnitus” by Folmer et al (2014) - De Ridder, Dirk (2015)
Fil: De Ridder, Dirk. University of Otago; Nueva Zelanda